The small quinolone derived compound HT61 enhances the effect of tobramycin against Pseudomonas aeruginosa in vitro and in vivo. (April 2020) - Amison, R.T.; Faure, M.-E.; O'Shaughnessy, B.G.; Bruce, K.D.; Hu, Y.; Coates, A.; Page, C.P.
Abstract: HT61 is a small quinolone-derived compound previously demonstrated to exhibit bactericidal activity against gram-positive bacteria including methicillin-susceptible Staphylococcus aureus (MSSA) and methicillin-resistant Staphylococcus aureus (MRSA). When combined with the classical antibiotics and antiseptics neomycin, gentamicin, mupirocin and chlorhexidine, HT61 demonstrated synergistic bactericidal activity against both MSSA and MRSA infections in vitro . In this study, we investigated the individual antimicrobial activity of HT61 alongside its capability to potentiate the efficacy of tobramycin against both a tobramycin sensitive laboratory reference strain (PAO1) and tobramycin resistant clinical isolates (RP73, NN2) of the gram-negative bacteria Pseudomonas aeruginosa (P. aeruginosa). Using broth microdilution methods, the MICs of HT61 were assessed against all strains, as well as the effect of HT61 in combination with tobramycin using both the chequerboard method and bacterial time-kill assays. A murine model of pulmonary infection was also used to evaluate the combination therapy of tobramycin and HT61 in vivo. In these studies, we demonstrated significant synergism between HT61 and tobramycin against the tobramycin resistant P. aeruginosa strains RP73 and NN2, whilst an additive/intermediate effect was observed for P. aeruginosa strain PA01 which was further confirmed using bacterial time kill analysis. In addition, the enhancement of tobramycin by HT61 was also evident in in vitro assays of biofilm eradication. Finally, in vivo studies revealed analogous effects to those observed in vitro with HT61 significantly reducing bacterial load when administered in combination with tobramycin against each of the three P. aeruginosa strains at the highest tested dose (10 mg/kg).